(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
Since firearm weapons provide convenient mean of destroying human life from a considerable distance affording at time opportunity for the shooter to escape, the possibility of apprehension as well as of being over powered by a strong adversary, is substantially reduced it has been the weapon of choice for gangsters, terrorists, extremities, anti social and anti national elements for better service to their purpose. A study was conducted on 200 alleged cases of homicides. Different profiles from type of injuries by blunt force were evaluated. The incidence of homicidal deaths was observed as 13.03% with male preponderance and the commonest age affected was 21 to 40 yrs.